(u)Mzantsi Classics: Dialogues in Decolonisation from Southern Africa - Adriana Brook (Brock Education: a Journal of Educational Research and Practice)
Using a dialectical framework, this book interrogates the role that classics has played in southern Africa (Zimbabwe, Mozambique, and especially South Africa) from diverse perspectives, from the earliest European colonizers to the Fallist protests of 2015/2016.  While (u)Mzantsi Classics is grounded in the historical and contemporary realities of the African south, Canadian readers will find many parallels with the vital issues confronting our own universities today. Both candid and hopeful, this book makes a compelling case for the role that classics can play in helping us to understand and navigate an increasingly polarized world.